Imaging Recommendations for Diagnosis, Staging, and Management of Penile Cancer - Sequeira, Rachel; Katdare, Aparna; Popat, Palak; Sable, Nilesh; Gala, Kunal; Chandra, Daksh; Agrawal, Archi; Prakash, Gagan; Murthy, Vedang; Menon, Santosh; Joshi, Amit; Singh, Ajaykumar; Kulkarni, Suyash (Indian Journal of Medical and Paediatric Oncology, 2023)
Penile cancer is more common in developing countries and presents unique challenges in treatment, given the psychological impact of surgical treatment options on patients. While clinical assessment of the lesions and nodal disease is critical, imaging does play a role in initial staging, response assessment, and surveillance. This article aims to delineate the guidelines for clinical and radiological evaluation of penile cancers and the approach to disease management.
Keywords: guidelines; imaging; penile cancer; recommendations